Inductive algebras for the motion group of the plane - Sharma P.; Vemuri M.K. (My University, 2025)
Each irreducible representation of the motion group of the plane has a unique maximal inductive algebra, and it is self-adjoint. © African Mathematical Union and Springer-Verlag GmbH Deutschland, ein Teil von Springer Nature 2025.